PENYULUHAN DAGUSIBU OBAT PADA SISWA SMAN 1 PARONGPONG - Sopian, Ahmad; Oktaviani, Dea Tri; Agustina, Selima Aileen; Riadi, Resti Fauzi; Sofiatus S, Deviana Imanda; Jaojah, Siti; Aditya, Rindang; Nuri Maharani, Anggi (Jurnal Bakti untuk Negeri, 2024)
In today's society, substance abuse is rampant, both prescription drugs and drugs purchased on their own initiative. One of the problems associated with drug use that is often encountered in the community is errors in self-medication or self-medication practices caused by a lack of knowledge about drugs and their use, so that in some cases poisoning and drug overdose can cause death. This counseling aims to increase the knowledge and understanding of the community regarding how to obtain, use, store and dispose of drugs properly. The method used in this research is by counseling to students of SMAN 1 Parongpong. DAGUSIBU counseling was held on Friday, November 24, 2023 at SMAN 1 Parongpong with 31 participants. The first counseling began with an explanation of the general definition of drugs and drug classification, the second explanation of how to get drugs properly and correctly, the third explanation of how to use drugs properly and correctly, the last explanation is about how to dispose of drugs properly and correctly. This activity increased the participants' knowledge of how to manage drugs properly and can increase public knowledge   Keywords: Medicine, Use, Management